Temporal analysis of mortality from urolithiasis in Brazil (2013-2023): an ecological study using DATASUS data (Brazilian Journal of Health Research, 2025)
Introduction: Urinary lithiasis results from salt aggregation in urine, referred to as nephrolithiasis when located in the kidneys and urolithiasis when present in the urinary tract. In Brazil, although epidemiological data are publicly available, no study has characterized mortality from urinary lithiasis, resulting in a gap in knowledge on this topic. Objectives: To perform an epidemiological and temporal analysis of overall and proportional mortality rates from urinary lithiasis in Brazil from 2013 to 2023, using DATASUS secondary data. Methods: This retrospective observational study used data from the Mortality Information System (SIM/DATASUS) covering the period from 2013 to 2023. Deaths caused by urinary lithiasis (ICD-10: N20 to N23) were included, and analyses were performed according to sex, age, race/skin color, and region. General and proportional mortality rates were calculated using annual population estimates from the Brazilian Institute of Geography and Statistics (IBGE). Results: The highest mortality rates due to lithiasis were observed among women, white individuals, with an average age of 67 years. Temporal changes in lithiasis mortality were observed over the 10-year period; on average, there were 0.09 deaths per 100,000 inhabitants, and the proportional mortality rate was 0.01% (1 in 10,000 deaths). Conclusion: Although urinary lithiasis accounts for only 0.01% of registered deaths, it is a preventable cause with appropriate treatment. Given its significant risk for complications such as sepsis, especially in older adults and individuals with comorbidities, the true mortality from lithiasis is likely underestimated in the available data.
Keywords: Urolithiasis; Mortality; Epidemiology; Brazil; Public health